Hip Resurfacing Arthroplasty and Perioperative Blood Testing. (1st October 2014) - Cook, Andrew; Cook, Steven; Smith, Ian; Weinrauch, Patrick
Abstract : It is standard practice in many institutions to routinely perform preoperative and postoperative haemoglobin level testing in association with hip joint arthroplasty procedures. It is our observation, however, that blood transfusion after uncomplicated primary hip arthroplasty in healthy patients is uncommon and that the decision to proceed with blood transfusion is typically made on clinical grounds. We therefore question the necessity and clinical value of routine perioperative blood testing about the time of hip resurfacing arthroplasty. We present analysis of perioperative blood tests and transfusion rates in 107 patients undertaking unilateral hybrid hip resurfacing arthroplasty by the senior author at a single institution over a three-year period. We conclude that routine perioperative testing of haemoglobin levels for hip resurfacing arthroplasty procedures does not assist in clinical management. We recommend that postoperative blood testing only be considered should the patient demonstrate clinical signs of symptomatic anaemia or if particular clinical circumstances necessitate.